Total congenital anonychia. A case report. - Sotiriou, E.; Devliotou, D.; Sotiriadis, D. (European Journal of Pediatric Dermatology, 2004)
Congenital absence of all nails is a rare anomaly. It is usually associated with malformations of ectodermal or mesodermal origin and is part of syndromes or it can be isolated. Here is reported a 2-year-old female with total congenital anonychia. Complete physical examination of the child revealed no abnormalities. X-ray of the hands and feet demonstrated no underlying deformities.